2003
DOI: 10.1167/iovs.02-0911
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Embryonic Development in the Mouse Eye by Ultrasound Biomicroscopy

Abstract: UBM allows noninvasive assessment of ocular morphogenesis in vivo and can be used to calculate relative growth rates of ocular structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 16 publications
5
44
0
Order By: Relevance
“…Other studies have already indicated the possibility of obtaining real-time in vivo skeletal muscle images of rats using high-resolution ultrasound. For instance, UBM has been used to study embryonic development through in utero images of small animals (Foster, 2003;Foster et al, 2002) and Witte et al (Witte et al, 2004) used UBM to describe the coordination of individual fibers of a rat and a mouse through ex vivo tests.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have already indicated the possibility of obtaining real-time in vivo skeletal muscle images of rats using high-resolution ultrasound. For instance, UBM has been used to study embryonic development through in utero images of small animals (Foster, 2003;Foster et al, 2002) and Witte et al (Witte et al, 2004) used UBM to describe the coordination of individual fibers of a rat and a mouse through ex vivo tests.…”
Section: Introductionmentioning
confidence: 99%
“…Unauthorized reproduction of this article is prohibited. [12], cow [29], and human [27] data. The gray lines fit the periods of exponential growth in each species.…”
mentioning
confidence: 99%
“…To quantify this effect, the eye volumes of the embryos were quantified with our previously published technique [54]. Briefly, the eye was modeled as an oblate spheroid [55], and the minor (along the optical axis) and major (orthogonal to the optical axis) axes lengths were obtained from the scaled OCT and OPT images. The volume was calculated by: …”
Section: Quantification Of Eye Volumesmentioning
confidence: 99%